Polygamy and Child Adoption in Islamic Law: A Comparative Study of Thought Muhammad Quraish Shihab and Zakir Naik - Muzzakir, Muzzakir; Anzaikhan, M.; Azwir Abdul Azis, Fouza (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
This article discusses the divergent opinions of the applicability of Islamic law to child adoption and polygamy, which have caused scholarly controversy because of different interpretations among modern experts. Muslims find it difficult to comprehend and apply these two ideas in line with religious teachings because of this discrepancy. The research employs a qualitative methodology along with a comparative study technique and descriptive analysis to address this discontent. Information was gathered from a variety of primary and secondary sources, including Muhammad Quraish Shihab and Zakir Naik's books and speeches. The results show that Muhammad Quraish Shihab uses a contextual approach that prioritizes justice in polygamy and preserving the lineage of adopted children while still giving full safety. However, Zakir Naik maintains a strict textual perspective, rejects child adoption because it could obstruct the application of other Islamic precepts, and views polygamy as a shari'ah right that does not require societal adjustment.